The theoretical description for sulfite vanadium(III)-oxyhydroxide-assisted electrochemical determination in natural water and beverages - Tkach, Volodymyr; Kushnir, Marta; Oliveira, Sílvio C.; Garcia, Jarem; Ivanushko, Yana; Nazymok, Yevgeniya; Morozova, Tetiana; Yagodynets, Petro; Khmeliar, Inesa; Kushnir, Lesya; Shahiieva, Raisa; Vitriak, Oksana; et al. (My University, 2022)
Sulfite is the ion of sulfurous acid, correspondent to tetravalent sulfur. It is used as a conservant in food industry and in beverage production. On the other hand, sulfite is an ecological marker for acid rains occurrence, which may be highly (eco)toxic, reason why its determination is really actual. Being a tetravalent sulfur derivative, sulfite may be either oxidized or reduced. In the case of cathodic reduction, the elemental sulfur or sulfide-ion may be a product, depending on pH.

Сульфіт - це іон сірчистої кислоти, що відповідає чотиривалентної сірці. Використовується як консервант в харчовій промисловості і у виробництві напоїв. З іншого боку, сульфіт є екологічним маркером виникнення кислотних дощів, які можуть бути високо (екологічними) токсичними, тому його визначення дійсно актуальне. Будучи чотиривалентним похідним сірки, сульфіт може як окислюватися, так і відновлюватися. У разі катодного відновлення елементарна сірка або сульфід-іон може бути продуктом, в залежності від рН.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; sulfite; сульфіт; консервант (виноробство)